Modelling primary blast lung injury - Scott, Timothy E. (2020)
Primary blast lung injury is the most important component of a multisystem syndrome of injury resulting from exposure to an explosive shockwave. The fact that it occurs in areas of conflict or following unpredictable industrial accidents makes clinical study implausible. Research in this field is therefore reliant on the use of some form of biological or non-biological surrogate model. Following a description of the epidemiology of the disease in a recent conflict, we describe the development of a new disease simulator and further explore its subsequent use in assessing treatment options both in the pre-hospital and intensive care environment.